Cardiovascular toxicity induced by TKIs in patients with chronic myeloid leukaemia: Are women and men different? - Cristina Madaudo; Daniela Di Lisi; Antonio Cannatà; Federica Manfrè; Celeste Vullo; Marco Santoro; Ciro Botta; Salvatrice Mancuso; Sergio Siragusa; Alfredo Ruggero Galassi; Giuseppina Novo (ESC Heart Failure)
Abstract Aims Knowledge of the effects of sex in cardio‐oncology is limited, particularly in patients treated with tyrosine kinase inhibitors (TKIs) for chronic myeloid leukaemia (CML). This study aims to evaluate the influence of gender differences on the incidence of cardiovascular toxicity in patients with CML. Methods The study population consisted of 148 patients (45% women, mean age: 58 ± 14.2 years) diagnosed with CML treated with TKIs. The HFA‐ICOS score estimated cardiovascular risk. The HFA‐ICOS score revealed that 12% of men and 6% of women were categorized as very high risk while 45% of men and 50% of women fell into the high‐risk group. Myocardial ischaemia, peripheral artery disease, venous thromboembolism, pulmonary hypertension and new‐onset arterial hypertension during treatment with TKIs were recorded. Results The incidence of global events between men and women was comparable (35% vs 32%, P = 0.68). There were 33% who experienced a cardiovascular event during TKI therapy, with a significant sex difference in arterial thrombosis incidence (P = 0.02) and venous thrombosis incidence (P = 0.02). Patients treated with ponatinib had a 41% event rate, followed by nilotinib (32%) and imatinib (32%). The HFA‐ICOS score demonstrated greater predictive efficacy for events in the female group [area under the curve (AUC) = 0.797] compared with the male group (AUC = 0.537). Very high [hazard ratio (HR) 3.07; confidence interval (CI) 1.11, 8.47 P = 0.03] and high (HR 3.29; CI 1.17, 9.26 P = 0.02) HFA‐ICOS scores were associated with increased event risk, particularly in women. Diabetes was women's strongest predictor of events (HR 5.40; CI 1.37, 21.3 P = 0.01). Conclusions Our study showed a similar frequency of cardiovascular events between men and women. Accurate cardiovascular risk stratification with HFA‐ICOS score in cancer patients is crucial. Diabetes and the HFA‐ICOS score were significant predictors of events in the female groups. A sex approach in clinical practice could be pursued to improve the appropriateness of care.